Hubungan Pengetahuan Pasangan Usia Subur dengan Pemakaian Kontrasepsi IUD di Desa Manunggal Kec. Labuhan Deli Tahun 2023 - Megawati Saragih; Sri Rezeki (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
The low coverage of PUS (Couples of Childbearing Age) regarding the use of IUD contraception certainly cannot be separated from the experience of family planning acceptors regarding the selection of contraceptives, because having good knowledge about certain contraceptive methods will change the perspective of acceptors in determining the most appropriate and effective contraception to use so that make contraceptive users more comfortable. The aim of the research is to determine the relationship between knowledge of couples of childbearing age and the use of IUD contraception in Manunggal Village, Labuhan Deli District, Deli Serdang Regency in 2023.The type of research carried out was descriptive analytical with a cross sectional approach, the population in the study was 321 acceptors using a random sampling system. The data collected in the research is primary data, namely data obtained directly from respondents. The data analysis used is chi square.The research results showed that the majority of respondents lacked knowledge, as many as 34 (44.7%) respondents did not use an IUD with a Chi square of 0.000.The conclusion is that there is a relationship between knowledge of couples of childbearing age and coverage of IUD contraceptive use in Manunggal Village, Labuhan Deli District, Deli Serdang Regency in 2023. It is hoped that all health workers in Manunggal Village will be able to encourage and develop the community to better maintain health and improve the health of couples of childbearing age so as to reduce risk of unwanted pregnancy